Extraction and Characterization of Dye Extract from Bridelia ferruginea - Joshua Yakubu; Andema Aaron Kanadi; Bifam Mathias; Peter Michael Dass (Kwaghe International Journal of Sciences and Technology, 2026)
Natural dyes have attracted increasing attention as sustainable alternatives to synthetic colorants, particularly because of their potential functional and bioactive properties. This study aimed to extract and characterize a natural dye from the stem of Bridelia ferruginea and evaluate its physicochemical, phytochemical, antimicrobial, thermal, morphological, and spectroscopic properties. The dye was extracted using the Soxhlet method, yielding 32%. The physical characterization showed that the extract was maroon in color, had a pH of 5.10, a melting range of 200–210°C, a density of 1.20, partial solubility in water, and complete solubility in methanol. Phytochemical screening revealed the presence of alkaloids, glycosides, flavonoids, terpenoids, saponins, tannins, and steroids, while phenols and anthraquinones were absent. The dye extract also inhibited the growth of selected bacterial and fungal organisms. Instrumental characterization was conducted using FTIR, UV–Visible spectroscopy, SEM, TGA, and GC–MS. FTIR analysis indicated the presence of O–H stretching, C–H stretching, C=C stretching, C–H bending, and C–O stretching vibrations. UV–Visible spectroscopy showed distinct absorption peaks, with the most prominent peak observed at 304 nm and an absorbance value of 2.4889. SEM analysis revealed compact, fused, and crystalline-like structures, while TGA indicated three stages of thermal stability: initial weight loss between 30 and 150°C, major weight loss between 250 and 450°C, and residual mass above 500°C. GC–MS analysis identified 18 compounds with their respective retention times and intensities; maltose showed the highest intensity at 2.50, whereas propanoic acid and tetral gyvcol showed lower intensities of 0.20. The study concludes that B. ferruginea stem extract possesses promising dye characteristics, bioactive constituents, antimicrobial potential, and measurable thermal stability. These findings contribute to the development of plant-based natural dyes for sustainable material and bioresource applications.